Statin Therapy for Primary Prevention in Adults Aged 80 Years and Older: A Systematic Review Conducted in Accordance with PRISMA 2020 - Francisco Epelde (Current Neuropharmacology, 2026)
Introduction: Statins are well established for the primary prevention of cardiovascular disease (CVD) up to approximately 75 years of age; however, direct evidence in adults aged 80 years and older remains limited. Extrapolation from younger populations is uncertain because advanced age is associated with greater competing mortality, frailty, multimorbidity, polypharmacy, and a shorter remaining time in which benefit can accrue. Methods: We conducted a systematic review in accordance with PRISMA 2020. A prespecified protocol was developed before screening. PubMed/MEDLINE, Embase, and Cochrane CENTRAL were searched through October 12, 2025. Eligible evidence comprised randomized trials, age-stratified trial analyses, pooled or individual-participant meta-analyses, systematic reviews with age-stratified quantitative data, and adjusted observational cohorts of older adults without established atherosclerotic cardiovascular disease. Outcomes included major adverse cardiovascular events (MACE), myocardial infarction, stroke, all-cause and cardiovascular mortality, adverse events, cognition, disability, and functional outcomes. Risk of bias or methodological quality was assessed using RoB 2, the Newcastle-Ottawa Scale, or AMSTAR 2, as appropriate, and certainty of evidence was rated using GRADE. Results: Twelve studies or trial programs met the inclusion criteria. Randomized evidence directly applicable to adults aged 80 years and older was minimal. PROSPER enrolled participants up to 82 years of age but combined primary and secondary prevention; ALLHAT-LLT showed no benefit in adults aged 75 years and older; and JUPITER and HOPE-3 showed reductions in cardiovascular events among adults aged 70 years and older but included few octogenarians. Observational cohorts suggested lower mortality or cardiovascular event rates among statin users, although these estimates were limited by healthy-user bias, residual confounding, and heterogeneity in age strata and outcome definitions. A formal meta-analysis of the primary-prevention population aged 80 years and older was not feasible because no randomized trial provided a directly comparable, extractable estimate for this group and the observational estimates were clinically and methodologically heterogeneous. Discussion: Evidence supports statin benefit through approximately 75 years of age, but evidence beyond 80 years is indirect and of low to very low certainty. Benefit is most plausible in robust octogenarians at high cardiovascular risk who have sufficient life expectancy, whereas routine initiation is unlikely to offer meaningful benefit to frail adults with a limited prognosis. Conclusion: Current evidence is insufficient to support routine statin initiation for primary prevention in all adults aged 80 years and older. Decisions should be individualized through shared decision-making that considers baseline cardiovascular risk, frailty, life expectancy, time to benefit, treatment burden, potential drug interactions, and the patient’s goals while definitive evidence from ongoing late-life primary-prevention trials is awaited.